진행성 비소세포폐암 환자에서 Gemcitabine/Cisplatin을 이용한 동시 화학 방사선 요법 - 옥철호(Chul Ho Oak), 김자경(Ja Kyung Kim), 장리라(Lee La Jang), 문대성(Dae Sung Moon), 장태원(Tae Won Jang), 정만홍(Maan Hong Jung), 조성환(Sung Whan Cho), 정태식(Tae Sig Jeung) (Radiation oncology journal, 2008)
목 적: 국소 진행성 폐암에서 동시 항암화학 방사선 요법이 표준 요법으로 자리 잡고 있다. 그러나 항암제의 그 사용시기와 방법에 있어서는 확립된 바가 없어서 gemcitabine, cisplatin 병용화학요법과 동시 방사선치료의 치료효과 및 안전성을 확인하였다. 대상 및 방법: 동시 항암화학 방사선요법시 gemcitabine 500 mg/m2, cisplatin 30 mg/m2 요법은 2주 간격으로 환자의 순응도에 따른 방사선치료 기간의 변동을 감안해서 3∼4회 치료하는 것을 원칙으로 하였고 흉부방사선치료는 1일 1회 1.8 Gy 씩, 주5회 분할조사 하였으며, 원발병소와 종격동 및 전이를 나타낸 림프절을 포함한 부분에 50.4 Gy를 조사 후 질환이 진행되지 않았을 경우 원발 병소에 18 Gy를 추가 조사하였다. 공고 화학요법은 3주 간격으로 2∼3회 치료하였다. 치료반응의 판정은 동시 항암화학 방사선요법 후와 공고 화학요법 후에 각각 WHO의 판정기준에 따라 평가했다. 결 과: 29명의 대상 중, 동시 항암화학 방사선요법 후 완전관해는 1명(4%), 부분 관해는 20명(69%)이었고 공고 화학요법이 마친 후 치료 판정에서 완전 관해는 3명(10%), 부분 관해는 21명(72%)이였다. 중앙 생존 기간은 16개월(2.4∼39.2개월)이고 1년 생존율은 62.7%, 2년 생존율은 43.9%, 3년 생존율은 20%이었다. 치료 도중 독성의 빈도는 3도 이상의 과립구 감소증이 11명(37.9%)이었고 3도 이상의 식도염이 15명(51.7%)이 발생하였다. 2도 이상의 폐렴은 6명(20.7%)에서 발생하였다. 결 론: 국소진행성 비소세포폐암환자에서 gemcitabine 500 mg/m2과 cisplatin 30 mg/m2의 2주 간격 투여와 동시항암화학방사선치료는 높은 치료반응률을 나타내었다. 그러나 3도 이상의 식도염과 폐렴이 예상보다 많이 관찰되어 이에 대한 부작용을 줄이기 위한 적절한 방법들이 강구되어야 할 것이며, 항암제의 용량조절, 방사선조사량의 조절과 특수 방사선치료방법들의 개발이 필요하리라고 판단되었다. Purpose: In cases of locally advanced non-small cell lung cancer (NSCLC), concurrent chemoradiotherapy (CCRT) is the leading therapeutic modality. However, much controversy exists about the chemotherapeutic regimens and radiation methods. Materials and Methods: During concurrent chemoradiotherapy, three or four cycles of gemcitabine (500 mg/m²) and cisplatin (30 mg/m²) were administered every two weeks while 50.4 Gy of irradiation was administered in 28 fractions (once/day, 5 treatment days/week) to the tumor site, mediastinum, and the involved lymph node region. In addition, a booster irradiation dose of 18 Gy in 10 fractions was administered to the primary tumor site unless the disease progressed. Two or three cycles of consolidation chemotherapy were performed with gemcitabine (1,200 mg/m², 1st and 8th day) and cisplatin (60 mg/m²) every three weeks. Results: A total of 29 patients were evaluable for modality response. Response and treatment toxicities were assessed after concurrent chemoradiotherapy and consolidation chemotherapy, respectively. One patient (4%) achieved a complete response; whereas 20 patients (69%) achieved a partial response after concurrent chemoradiotherapy. Following the consolidation chemotherapy, three patients (10.3%) achieved complete responses and 21 patients (72.4%) achieved partial responses. The median follow-up period was 20 months (range 3∼39 months) and the median survival time was 16 months (95% CI; 2.4∼39.2 months). The survival rates in one, two, and three years after the completion of treatment were 62.7%, 43.9%, and 20%, respectively. Complications associated to this treatment modality included grade 3 or 4 esophagitis, which occurred in 15 patients (51.7%). In addition, an incidence of 24% for grade 3 and 14% for grade 4 neutropenia. Lastly, grade 2 radiation pneumonitis occurred in 6 patients (22%). Conclusion: The response rate and survival time of concurrent chemoradiotherapy with biweekly gemcitabine (500 mg/m²) and cisplatin (30 mg/m²) were encouraging in patients with locally advanced NSCLC. However, treatment related toxicities were significant, indicating that further modification of therapy seems to be warranted. KCI Citation Count: 0